WHITE-COAT HYPERTENSION AND MASKED HYPERTENSION IN HYPERTENSIVE KIDNEY TRANSPLANT RECIPIENTS. (April 2021) - Loutradis, Charalampos; Korogiannou, Maria; Xagas, Efstathios; Marinaki, Smaragdi; Argyris, Antonios; Protogerou, Athanasios; Sarafidis, Pantelis; Boletis, John
Abstract : Objective: Patients suffering from chronic kidney disease (CKD) have inadequate control of blood pressure (BP) ranging between 30 to 40%. In addition 35% of them have white-coat hypertension or masked hypertension. Recent epidemiologic data in the general population associate both of the aforementioned BP patterns with poor outcomes. The objective of this study is to examine the prevalence of these hypertension phenotypes in hypertensive kidney transplant recipients. Design and method: 150 kidney transplant recipients were included in this study. They underwent 24-hour ABPM with the Mobil-O-Graph NG device. Hypertension was defined as: (1) office BP (oBP) > or = 140/90 mmHg or use of antihypertensive agents, (2) ambulatory BP > or = 130/80 mmHg or use of antihypertensive agents. Patterns of BP control were defined as follows: (1) truly controlled BP (oBP < 140/90 and 24-hr BP < 130/80mmHg), (2) uncontrolled hypertension (oBP > or = 140/90 and 24-hr BP > or = 130/80mmHg), (3) white-coat hypertension (oBP > or = 140/90 and 24-hr BP < 130/80mmHg), (4) masked hypertension (oBP < 140/90 and 24-hr BP > or = 130/80mmHg). Results: The prevalence of hypertension was 88.0% according to office BP readings and 93.3% according to ABPM (p = 0, 112). 125 individuals (89, 3% of the total) were hypertensives receiving antihypertensive agents. Among them, according to office BP readings and 24-hr ABPM, 44 (31, 0%) hypertensive patients had BP control and 30 (21, 1%) had uncontrolled hypertension. Moreover, among the hypertensive patients, 10 (7, 0 %) had the white-coat hypertension phenotype and 58 (40, 8%) had masked hypertension (Fig 1). Figure. No caption available. Conclusions: The use of ABPM in kidney transplant recipients reveals low control of BP, low prevalence of white-coat hypertension and markedly high prevalence of masked hypertension. The last finding is particularly important, considering the established association between masked hypertension and increased cardiovascular risk.